2011
DOI: 10.1590/s0100-54052011000400008
|View full text |Cite
|
Sign up to set email alerts
|

Controle de oídio em pepino parternocárpico com produtos alternativos em cultivo protegido

Abstract: RESUMOO oídio é a doença mais importa nte para pepino partenocárpico em cu ltivo protegido na Regiã o Norte do Paraná, em períodos de ba ixa u mida de. As ca ra cterística s desse a grossistema propicia m condições favoráveis ao uso de medidas alternativas para o controle dessa doença. Assim, cinco produtos alternativo s fora m a va li a dos p a ra o co n t r ol e d e o í d i o e m pe p i n o p a r te n o c á rp i c o , h í b ri d o Hok u shin, em cu ltivo protegido: leite cru de va ca , óleo de nim, a c ibe n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
0
0
2
Order By: Relevance
“…Moreover, a considerable reduction in anthracnose was found in four of the samples (UFPB01, UFPB04, UFPB05 and UFPB18). These results are similar to findings described by FARIA et al (2011), who investigated the effect of applying citric biomass to the parthenocarpic cumber (Cucumis sativus L.) for the control of Oidium spp. The authors reported no differences among the treatments, but found a reduction in the area under the curve of odium progression.…”
Section: Resultssupporting
confidence: 90%
“…Moreover, a considerable reduction in anthracnose was found in four of the samples (UFPB01, UFPB04, UFPB05 and UFPB18). These results are similar to findings described by FARIA et al (2011), who investigated the effect of applying citric biomass to the parthenocarpic cumber (Cucumis sativus L.) for the control of Oidium spp. The authors reported no differences among the treatments, but found a reduction in the area under the curve of odium progression.…”
Section: Resultssupporting
confidence: 90%
“…Faria et al (2011) ao testarem diferentes produtos alternativos para o controle do oídio na cultura de pepino, verificaram melhor controle da doença ao utilizar óleo de neem, o qual foi superior ao fungicida químico sistêmico azoxystrobin.…”
Section: Resultsunclassified
“…e resíduo da fermentação glutâmica do melaço (BETTIOL; ASTIARRAGA, 1998), biofertilizantes (ISHIDA et al, 2001), extratos de plantas (DAAYF et al, 1995), sais de potássio (ZIV; ZITTER, 1992;KETTLEWEL et al, 2000), silício , extrato de neem (FARIA et al, 2011) e vinagre (OLIVEIRA et al, 2002.…”
unclassified